Electrochemical in Situ Synthesis of Polypyrrole Nanowires - Gacitua-Santalices, M; Gacitua-Santalices, M (Elsevier Inc., 2019)
Modification with polypyrrole nanowires, PPy-nw, is accomplished directly upon the working electrode by electrochemical polymerization methods using mesoporous silica as a template. The silica template is prepared by a potentiostatic method, generating a homogeneous film over a previously deposited thin layer of PPy, so that PPy-nw grows within the nanochannels of the mesoporous silica and adheres firmly to the surface. Subsequently the template is removed to obtain intact Pt|PPy-nw with stable and reproducible electrochemical properties, and with an enhanced (about 360 times higher charge capacity) response after charge–discharge experiments compared to equivalent electrodes modified with polymer deposits in the bulk (PPy) form. SEM reveals the brush-type conformation of PPy-nw (30 nm in diameter). Thus, a cheap, simple, highly repeatable method is used in situ to prepare electrodes modified with nano-structured polymers, using electrochemical techniques alone. This could have a great impact on a wide range of applications of conducting polymers. © 2019 The Authors